2018
DOI: 10.1155/2018/8467169
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Doxorubicin-Loaded Micelles Based on Glycyrrhetinic Acid Modified Gelatin Conjugates for Targeting Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent fatal diseases and the incidence of HCC is increasing worldwide. Polymeric micelles with targeting groups have drawn great attention as carriers for drug delivery in HCC therapy. Herein, novel glycyrrhetinic acid modified gelatin (GA-GEL) conjugates with three substitution degrees were synthesized and characterized. Doxorubicin (DOX) was applied as a model drug. DOX-loaded GA-GEL (DOX/GA-GEL) micelles were prepared by an emulsionsolvent evaporation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Other DDSs for treating cancer including polymers, micelles, lipid, CeO 2 , etc. also exhibited good binding affinity for DOX [ 58 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other DDSs for treating cancer including polymers, micelles, lipid, CeO 2 , etc. also exhibited good binding affinity for DOX [ 58 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it appeared that these micelles exhibited higher cellular toxicity to MDA-MB-231 cancerous cells than in normal cells (NIH-3T3). Novel glycyrrhetinic acid modified gelatin (GA-Gel) conjugates with three substitution degrees were synthesized and used for the preparation of Dox-loaded micellar systems by an emulsion–solvent evaporation method [ 160 ]. The encapsulation efficiency was 63.6–96.2%, and the loading content was 8.3–12.5%.…”
Section: Micellar Drug Delivery Systems Based On Proteinsmentioning
confidence: 99%
“…The decades of nanoscale research has resulted in several nanotheranostics and nanotherapeutics techniques being developed for the treatment of cancer (Bertrand, Wu, Xu, Kamaly, & Farokhzad, 2014;D. Fan et al, 2018) nanoscale drug delivery system is the polymeric micelles which comprises a core (inner realm) and shell (outer realm; Bromberg, 2008;Ji et al, 2018;Kataoka, Harada, & Nagasaki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric micelles have a unique advantage of being able to enclose the unstable drug in the core realm to avoid contact from the gastrointestinal contents which may damage or degrade it. Thus mixed micelles are being much sought after as they offer much‐needed stability of drug, improved release, and uptake of drug at the target tumor site, prolong its circulation time, and also are cytocompatible (Ebrahim Attia et al, ; D. Fan et al, ; Ji et al, ). Over decades, it has also been found that the micelles may reduce the potential side effects of the drug and thereby improve the therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation